Exploración minera, compañías mineras junior y aspectos a tomar en cuenta para su promoción - Torres Alvarez, Hernán (2015)
The author makes an analysis of the measures to be taken into account to promote mining activities, with special emphasis in the area of exploration as the main activity in the mining industry. Therefore, the present article focuses on everything that made such activity from its main actors to the considerations to take into account in its regulation and the effectiveness of it. Finally the author presents his conclusions focusing on the importance of generating investment and therefore expedition to implement the best mechanisms in the mining sector.